Bapsi Sidhwa: A Chronicle Of The Past Traumatic Memories - Katariya, Archana; Chaudhary, Priyanka (International Journal of Psychosocial Rehabilitation, 2020)
Much has been written about the holocaust that followed the Partition of India in 1947, but seldom has that story been told as touchingly view of Indian life can only be compared to V. S. Naipaul’s.”- Bloomsbury Review Literature plays a major role in the improvement of society. Society follows a specific path, and literature is always helpful in exposing all aspects of society in its replication. For all readers to understand, colonial literature has been written on a scorching theme, reflecting the truly connected conditions of history. The partition of India and the powerful exodus of citizens are both frightening and memorable events of history. Many authors emphasized the current state of colonial literature in their works. One of the most renowned authors, Bapsi Sidhwa was an eyewitness of the both colonized and post-colonized era. Her novels have a myriad of interpretations to identify the feminine point of view, several societal hitches and innumerable unseen and unheard stories. Being a Persian, she is impartialin the interpretation of the historical events, and besides inferring episodes as an observer. Her writings Cracking India and Pakistani Bride illustrates the frightening and the critical circumstances of the post-colonial period.